A Case Report of Autoimmune Polyglandular Syndrome - Murad, Rania Alsayed; Alakkad, Ashraf; Adwan, Anwar; Ramahi, Mikdam Al (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
A 60-year-old male patient, weighing 40 kg, having a BMI of 13, who was also a known case of Diabetes Mellitus Type II was shifted to the Orthopaedic Ward last month due to a fall, which led him to develop an intertrochanteric fracture in the femur. While the treatment of the patient was in an ongoing status for his fracture, his Diabetes was seen to be poorly controlled, with his blood glucose levels being constantly evaluated to be in a state of severe hypoglycaemia to slightly increased levels of blood glucose. On examination, the patient showed clear signs of being malnourished. He had creases on the palmar aspects of his hands and hyperpigmentation on his buccal mucosa. Furthermore, his lab reports revealed abnormalities in nearly every lab test ordered. Not only did he have elevated ACTH levels, but there was also a failure of Cortisol stimulation. His DEXA Scan showed that he was predisposed to develop severe osteoporosis and his malnourished condition was supportive of promoting that condition even more. The patient was diagnosed to be suffering from Autoimmune Polyglandular Syndrome, Type II. Women were more affected than men. This is a rare condition of one of its kind where there is a pre-existence of autoimmune adrenal insufficiency along with either autoimmune thyroid disease or autoimmune diabetes mellitus. Since this condition is rare, it tends to often get overlooked upon diagnosis, leading to misdiagnosis because almost all of the presenting features or the symptoms of the prevalent endocrinological disorders present in this condition mimic either hypothyroidism, or diabetes, or adrenal insufficiency alone, and thus lead to further consequences when the condition does not resolve despite persistent treatment, such as the case in this patient. This paper reviews the background of the patient and the causes that possibly could have made him reach this advanced stage of the disease. The paper also reflects upon the disease, Autoimmune Polyglandular Syndrome Type II, as a whole and elaborates on the symptoms and signs which the patient tens to confuse with other endocrinological diseases. Lastly, this paper shall also review the appropriate management plan for the patient to ease his symptoms and accelerate his recovery process.